Prolonged antibiotic administration for surgical site infection in pediatric laryngotracheal surgery. (27th December 2018) - Torre, Michele; Paraboschi, Irene; Loy, Anna; Mesini, Alessio; Pistorio, Angela; Simonini, Alessandro; Mattioli, Girolamo; Mazzei, Oscar; Piro, Liliana; Bandettini, Roberto; Castagnola, Elio
Abstract : Objectives/Hypothesis: Incidence of surgical site infection (SSI) after laryngotracheal (LT) surgery is relatively high, especially in children. Study Design: Retrospective and prospective cohort study. Methods: Clinical records of children who underwent open LT surgery at the Istituto Giannina Gaslini Children's Hospital from January 2008 to August 2017 were reviewed for development of SSI. Standard antibiotic prophylaxis was administered until February 2015. In March 2015, an antibiotic treatment tailored on pathogens isolated from surveillance cultures and prolonged until extubation was introduced. Incidence and risk factors for SSI before and after the new protocol implementation were analyzed by means of univariate and multivariable analyses. Results: A total of 57 procedures were analyzed. SSI incidence was 36% in patients receiving standard prophylaxis and 4% in those treated with the new strategy ( P = .004), with an absolute benefit increase of 32% (95% confidence interval: 11%–52%), in absence of any difference in clinical conditions between the two groups. Conclusions: The new management protocol had a highly favorable impact on the development of an SSI. Level of Evidence: 2b Laryngoscope, 129:2634–2639, 2019